Thermal sensing using micro-ring resonators in optical network-on-chip - Liu, Weichen (2020)
In this paper, we for the first time utilize the micro-ring resonators (MRs) in optical networks-on-chip (ONoCs) to implement thermal sensing without requiring additional hardware or chip area. The challenges in accuracy and reliability that arise from fabrication-induced process variations (PVs) and device-level wavelength tuning mechanism are resolved. We quantitatively model the intrinsic thermal sensitivity of MRs with finegrained consideration of wavelength tuning mechanism. Based on it, a novel PV-tolerant thermal sensor design is proposed. By exploiting the hidden `redundancy' in wavelength division multiplexing (WDM) technique, our sensor achieves accurate and efficient temperature measurement with the capability of PV tolerance. Evaluation results based on professional photonic component and circuit simulations show an average of 86.49% improvement in measurement accuracy compared to the state-of-the-art on-chip thermal sensing approach using MRs. Our thermal sensor achieves stable performance in the ONoCs employing dense WDM with an inaccuracy of only 0.8650 K.